“Rendimiento del cultivo de lechuga (lactuca sativa) variedad great lakes 659 con la aplicación de fosfonato de calcio-provincia de Lamas” - Rojas Hidalgo, Luis Antonio (2015)
This research ütled "CROP YIELD OF LETTUCE (Lactuca saliva) GREA T LAKES 659 VARIETY TO THE IMPLEMENTATION OF calcium phosphonate - PROVINCE OF lAMAS, aimed to evaluate the effect of calcium phosphonate in vegetative crop development. As well as making the economic analysis of the treatments under study and evaluate four treatments~ TO (no apptication). T1 (0.25 kg ha-1 of calcium phosphonate), T2 (O.SO kg ha-1 of phosphonate calcium) and T3 (0.75 kg ha-1 of calcium phosphonate) T4 (1.0 kg ha-1 of calcium phosphonate). The parameters evaluated were root collar diameter, plant length, number of leaves, plant weight, production yietd in t.ha-1 and economic analysis of all treatments studied. The results indicates that treatment T4 (calcium phosphonate kg.ha-1) was the most critica! with a performance of 42 856,25 kg/ha-1, with a value of B/C of 2.63 and net profit by has S/. 21 265,54 new soles respectively.